2005
DOI: 10.1080/10473289.2005.10464652
|View full text |Cite
|
Sign up to set email alerts
|

Bioaerosol Generation at Large-Scale Green Waste Composting Plants

Abstract: Bioaerosol release from composting plants is a cause of concern because of the potential health impacts on site workers and local residents. A one-year monitoring was undertaken in a typical composting plant treating green wastes by windrowing in the open. Aspergillus fumigatus spores and mesophilic bacteria were used as monitoring parameters and were collected in a six-stage Andersen sampler impactor from the air at different locations and during different operational activities. Background concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 13 publications
1
26
0
Order By: Relevance
“…This is in line with most other studies concerning the distances of microbial dispersion from biological waste treatment applications. 17,18 In the farming environment we did not see any significant differences in microbial levels between different distances from the cowshed. The concentrations remained within the range of background rural areas.…”
Section: Dispersion Of Microbes To the Environmentmentioning
confidence: 86%
See 1 more Smart Citation
“…This is in line with most other studies concerning the distances of microbial dispersion from biological waste treatment applications. 17,18 In the farming environment we did not see any significant differences in microbial levels between different distances from the cowshed. The concentrations remained within the range of background rural areas.…”
Section: Dispersion Of Microbes To the Environmentmentioning
confidence: 86%
“…However, most studies have reported much smaller distances where elevated microbial levels can be analyzed. Sanchez-Monedero et al 17 detected an approximately 100-fold increase in the concentrations of viable A. fumigatus and mesophilic bacteria 40 m downwind of a composting site during different activities in large-scale green waste composting plant in northern England. However, no significant differences to background levels were found any longer at distances of 200 and 300 m from the operational area.…”
Section: Introductionmentioning
confidence: 99%
“…Mean daily Penicillium/Aspergillus type spores concentrations have also been shown to be higher on-site (3,207 spores m -3 ) than off-site (264 spores m -3 ) (Hryhorczuk et al 2001). At a full scale composting facility, samples collected 25-40 m downwind showed increases in concentration of A. fumigatus up to two orders of magnitude from 3 · 10 2 to 5 · 10 4 cfu m -3 when the compost was turned, or during some other compost disruption event (Sanchez-Monedero et al 2005). Another study found A. fumigatus spore concentrations close to compost piles sometimes exceeded 10 6 cfu m -3 (Clark et al 1983).…”
Section: Introductionmentioning
confidence: 92%
“…Previous investigations have largely studied bioaerosol from composting plants or facilities (Van der Werf 1996;Folmsbee and Strevett 1999;Hryhorczuk et al 2001;Sanchez-Monedero et al 2005;Taha et al 2006). A few studies have looked at bioaerosol release from land application of biosolids and potential hazards posed by this (Pillai et al 1996;Gerba et al 2002;Brooks et al 2004;Brooks et al 2005); however, it seem that data relating to bioaerosol emissions as a result of application of municipal solid waste (MSW) compost are lacking.…”
Section: Introductionmentioning
confidence: 96%